Effects on learning and satisfaction of using flipped classroom and authentic assessment in university maths for engineering freshmen - Maluenda Albornoz, Jorge (2021)
The high failure rates in Introduction to University Mathematics (IUM) caused the investigation to develop an intervention based on the incorporation of flipped classroom and authentic assessment to reverse this situation. The objective of the present study was to evaluate the effect of the implementation of these two approaches on the performance of engineering freshmen at IMU. A quasi-experimental study was carried out with a control and intervention group, as well as pre and post-test to measure learning and student satisfaction. The results showed statistically significant differences in the overall results and for each evaluation favorable to the changed section, reflecting an 18.5% improvement in academic results. In addition, greater general satisfaction was observed in this section, which shows a general utility of the intervention to contribute in both aspects.